PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR - Septiana Andeswari; Dudung Amir Sholeh; Linda Zakiyah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This study was conducted to determine the development and feasibility of learning media student worksheets (LKPD) based on Problem Based Learning in learning mathematics for grade IV elementary schools. The research method used in this study is research and development (Research and Development) which uses four stages of the Borg and Gall research and development model, namely: 1) research and information collecting, 2) Planning, 3) develop preliminary form a product, 4) preliminary field testing 5) main product revision, 6) main field testing 7) operational product revision 8) operational field testing, 9) final product revision, 10) desimination. The result of this research and development is a problem based learning LKPD product in the fourth grade elementary school mathematics learning. The feasibility level based on the results of the percentage assessment  of  material  experts,  learning  media  experts,  and  linguists  respectively  got 90.47%, 82.28%, and 73.3% with the criteria of "very feasible". Furthermore, the response of students to the product when it was tested in the main field testing stage of the LKPD problem based product also did not require improvement and got a percentage of 95.17% with the criteria of "very good". Based on the results of interviews with fourth grade teachers, teachers are interested   in  using  problem-based   learning   LKPD  products   in   mathematics learning activities in the classroom. Based on this, it can be concluded that problem-based learning LKPD is appropriate to be used as one of the mathematics teaching materials in geometry learning.